2023
DOI: 10.1155/2023/5560560
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Dysfunction in Patients with Liver Cirrhosis and Splenomegaly and Its Countermeasures: A Retrospective Study of 1522 Patients

Abstract: Objective. Patients with cirrhosis and splenomegaly often have coagulation dysfunction which affects treatment and prognosis. This study explores the status, grading, and treatment strategies of coagulation dysfunction in patients with liver cirrhosis and splenomegaly. Methods. A retrospective cohort study was conducted on the clinical data on consecutive patients with cirrhosis and splenomegaly treated at Hainan General Hospital, China, from January 2000 to December 2020. Starting research in January 2022. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Papain was evaluated via in vitro study using PT and PTT assays, which can be used to study the extrinsic and intrinsic coagulation cascade. PT assays primarily involve procedures that initiate the extrinsic coagulation factor (factor VII) and common (factors II, V, and X) pathways, as well as fibrinogen [43], whereas the aPTT assay involves procedures that initiate intrinsic coagulation system, comprising factors VIII, IX, XI, and XII [44]. In this study, we found that papain is able to prolong PT and aPTT even at a concentration of 8 U/mL Prolongation of PT can be due to a deficiency in any of the factors involved in the extrinsic and common pathways of blood coagulation or the presence of papain.…”
Section: Discussionmentioning
confidence: 99%
“…Papain was evaluated via in vitro study using PT and PTT assays, which can be used to study the extrinsic and intrinsic coagulation cascade. PT assays primarily involve procedures that initiate the extrinsic coagulation factor (factor VII) and common (factors II, V, and X) pathways, as well as fibrinogen [43], whereas the aPTT assay involves procedures that initiate intrinsic coagulation system, comprising factors VIII, IX, XI, and XII [44]. In this study, we found that papain is able to prolong PT and aPTT even at a concentration of 8 U/mL Prolongation of PT can be due to a deficiency in any of the factors involved in the extrinsic and common pathways of blood coagulation or the presence of papain.…”
Section: Discussionmentioning
confidence: 99%
“…In MASLD patients, there is also an alteration of the levels of antithrombin and von Willebrand factor (vWF) [66,67], whose altered activation of the latter leads to the dysregulated formation of a platelet plug [66]. The severity of alteration in hemostasis was more pronounced in patients with advanced liver disease such as MASH or cirrhosis [68,69], in which more advanced hepatocellular damage is present [59]. Hepatocellular damage of a significant degree could result in a compromised production of various coagulation factors, including fibrinogen; thrombin; and factors V, VII, IX, and X.…”
Section: Coagulation Dysfunctionsmentioning
confidence: 99%
“…Hepatocellular damage of a significant degree could result in a compromised production of various coagulation factors, including fibrinogen; thrombin; and factors V, VII, IX, and X. These factors are predominantly synthesized in the liver [68,69]. As a result, this gives rise to an increased vulnerability to both thrombotic and hemorrhagic events [68,69].…”
Section: Coagulation Dysfunctionsmentioning
confidence: 99%
See 1 more Smart Citation